Work process in mental health and the psycosocial area (Revista Latino-Americana de Enfermagem, 2005)
We present a theoretical reflection about determinants and constitutive elements of the nursing work process in the psychiatric and psychosocial areas, in the context of the Brazilian Psychiatric Reform. The aim is to offer theoretical and conceptual guidance with a view to mental health workers' reflexive action, particularly in nursing. The purpose of this article is to preserve the memory of nursing practice in psychiatry and to go beyond, with a view to constructing the psychosocial area, supporting teaching in all fields of health knowledge.